Implementasi Protokol MQTT Untuk Sistem Monitoring Perangkat IoT - Zavero Brillianata Abilovani; Widhi Yahya; Fariz Andri Bakhtiar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Internet era at this time has developed a technology called Internet of Things as known as IoT. Where IoT is able to transmit data automatically from computer to computer without the initiation from humans. However, with size and number of data that increased will be transmitted make IoT devices performance has a negative result. Efforts are being made to overcome these problems, namely the need for a system that is able to manage devices and can monitor and maintain availability of IoT devices. One way is to make an IoT device monitoring system that aims to monitor when there is a disruption to the device. By implementing the MQTT protocol which is a protocol that implements the publish-subscribe mechanism and runs on the application layer. The MQTT protocol can process the send and receive of messages to manage and monitor according to the user's wishes, because the send and receive of messages by predetermined topics. Based on results rather than testing, the MQTT protocol has a smaller resource requirement than the UDP protocol and has a smaller data packet size than the SNMP protocol. The IoT device monitoring system that uses the MQTT protocol also has a small delay of 0.008634 sec and a throughput value of 9.2 MBit / sec. So that the system can run on low bandwidth and high latency.